Using Comic Strips as Media to Teach Writing in EFL Classroom - S., Kartika (Journal of Linguistics and Social Sciences, 2024)
Media of teaching applied in the classroom gives an effect on the class atmosphere and the writing result. Comic strips can be used as media in teaching learning process of writing. It is a sequence of history that usually contains, almost all the elements: character, plot, dialogues, conflict and climax. It has a story line which has a conclusion or at times a punch. It also can be used to teach writing for all grade students. This paper aims to promote comic strips as media to teach writing and to present the activities using comic strips. The teaching media, Comic strips and the activities of using comic strips as media in teaching writing will be presented. These sorts of activities are adaptable to students of various levels, but within this paper specific levels are targeted. This paper is expected to be useful in order to give a contribution to the development of educational world especially to the process of teaching writing.